Relationship between Upazila Nirbahi Officer(UNO) and Upazila Chairmen(UZC): study on two(2) upazila parishad - Afroz, Hosna (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2013.